IgM Flare in Anti-MAG Neuropathy Post Rituximab Treatment: A Clinical Case and a Systematic Review of the Literature - Giovanni Siconolfi; Francesca Vitali; Maria Ausilia Sciarrone; Michelangelo Ardito; Valeria Guglielmino; Angela Romano; Giuseppe Granata; Gabriella Silvestri; Marco Luigetti (Brain Sciences)
Background/Objectives: Anti-MAG polyneuropathy is a demyelinating peripheral neuropathy associated with IgM monoclonal gammopathies, particularly MGUS (monoclonal gammopathy of undetermined significance) and Waldenström macroglobulinemia. It is characterized by a subacute onset of distal sensory symptoms, with distal motor dysfunction typically appearing only in the later stages of the disease. The condition is caused by the presence of autoantibodies directed against myelin-associated glycoprotein, a structural protein of myelin. This leads to abnormalities in electrophysiological studies, such as markedly delayed distal latencies without conduction blocks or temporal dispersion of potentials. While rituximab (RTX) is the primary treatment, its efficacy is limited, with improvement seen in only 30–50% of patients. Recently, acute worsening of symptoms after RTX treatment has been increasingly reported. Methods: This systematic review compiles case reports and series from inception to June 2024 published on Scopus, PubMed or Cochrane, documenting acute exacerbations after RTX treatment in patients with anti-MAG polyneuropathy. Additionally, we present a case report from our institution that highlights this phenomenon. Results: We identified 13 clinical cases of acute deterioration in patients with anti-MAG polyneuropathy. Among these, eight patients (62%) achieved full recovery following additional treatment, while five patients (38%) did not return to their previous level of function. Plasmapheresis led to complete recovery in all four patients who received this intervention. Interestingly, many patients also experienced recovery after discontinuation of rituximab (RTX) treatment without the need for further therapeutic intervention. Conclusions: Acute clinical deterioration following RTX treatment in anti-MAG polyneuropathy is a possible occurrence. However, to date, no studies have assessed the true prevalence of this phenomenon. Further research is warranted to identify potential predictors of worsening following RTX treatment in this patient population.